Yarn evenness parameters optimization in jetring spinning process - Gulsevincler, Ekrem; Usal, Mustafa Resit; Yilmaz, Demet (Informa UK Limited, 2019)
In this study, the effects of air nozzles called jetring or nozzlering, on yarn quality which is used as an additional process in conventional ring spinning machines have been investigated. The res...